Pattern of Clinicopathological Features of Head and Neck Cancer Patients in a Tertiary Level Specialized Hospital in Dhaka, Bangladesh - Masud, Md Rakibul Islam; Khan, Mojibur Rahman; Bhuiyan, Md Jahin Tareq; Tuly, Badrun Nahar; Islam Pathan, Mohammad Saiful (Community Based Medical Journal, 2022)
A cross-sectional, descriptive study was conducted to see the pattern of clinicopathological features of head and neck cancer patients in a tertiary level hospital. The study was conducted between January and April of 2017 in National Institute of Cancer Research & Hospital (NICRH), Dhaka, Bangladesh. Data was collected from a total number of 69 histopathologically and clinically confirmed patients. A male predominance (2.14:1) was noted except for oral cavity cancer (1:1). Mean age for males and females were (56.15±11.47) years and (54.50±7.16) years respectively. Positive history of associated factors like smoking (60.34%), betel nut and betel leaf (81.36%), smokeless tobacco (56.90%) was prevalent among majority of the participants except for alcohol (6.90%). Smoking was prevalent only among males. Knowledge regarding the role of associated factors was very poor, e.g., smoking (10.61%), betel nut & leaf (7.58%), smokeless tobacco (6.06%), alcohol (7.58%) for causing cancer. 10.71% patients gave positive family history of cancer (1st degree relative). 27.59% patients gave history of treatment by homeopathy/traditional healers. The most common sites of cancer in males were larynx (27.3%) followed by oral cavity (20.5%). In case of female patients, most common sites were oral cavity (40.9%) followed by larynx (22.7%). Most common histopathological type was squamous cell carcinoma (91.94%). Lymph node metastasis were present in 47.62% patients, whereas only 1.56% patients had distant metastasis and 3.13% had recurrent/residual disease. 18.64% patients gave history of definitive surgery. To conclude, most of the patients usually reported with advanced stages of cancer; however, preventable factors were found among all of them. Unfortunately, they had very poor knowledge about those preventable factors which warrants an immediate and elaborate public health program to fill up this vast gap of knowledge. Prevention and early diagnosis should be main arsenal to combat head and neck cancer. CBMJ 2022 July: vol. 11 no. 02 P: 108-113